Umar ibn al-Khattab: the second of the four rightly-guided caliphs - Maulvi Abdul Aziz (Riyadh: Darussalam, 2012)
Darussalam, presents the entire History of Islam to our youth in language that appeals to them, in a simple yet lucid manner. The first four volumes in this series explore Islamic history during the period of the first Four Rightly-Guided Caliphs. Later volumes are devoted to the History of Islam. This book covers the Second Caliph, Umar ibn al-khattab (R.A).